Randomized controlled trial of standard versus double dose cotrimoxazole for childhood pneumonia in Pakistan - Rasmussen, Zeba A.; Bari, Abdul; Qazi, Shamim; Rehman, Gul; Azam, Iqbal; Khan, SherBaz; Aziz, Farida; Rafi, Sadia; Roghani, Mehr Taj; Iqbal, Imran; Nagi, Abdul Ghaffar; Hussain, Waqar; et al. (World Health Organization, 2005)
Objective Increasing concern over bacterial resistance to cotrimoxazole, which is recommended by WHO as a first-line drug for treating non-severe pneumonia, led to the suggestion that this might not be optimal therapy. However, changing to alternative antimicrobial agents, such as amoxicillin, is costly. We compared the clinical efficacy of twice-daily cotrimoxazole in standard versus double dosage for treating non-severe pneumonia in children. Methods A randomized controlled multicentre trial was implemented in seven hospital outpatient departments and two community health programmes. A total of 1143 children aged 2–59 months with non-severe pneumonia were randomly allocated to receive 4 mg trimethoprim plus 20 mg sulfamethoxazole/kg of body weight or 8 mg trimethoprim plus 40 mg sulfamethoxazole/kg of body weight orally twice-daily for 5 days Treatment failure occurred when a child required a change of therapy, died or was lost to follow-up. Children required a change of therapy if their condition worsened (they developed chest indrawing or danger signs) or if at 48 hours after enrolment, their clinical condition was the same (defined as having a respiratory rate that was 5 breaths/minute higher or lower than at the time of enrolment). Findings The results of 1134 children were analysed: 578 were assigned to the standard dose of cotrimoxazole and 556 to the double dose. Treatment failed in 112 children (19.4%) in the standard group and 118 (21.2%) in the double-dose group (relative risk 1.10; 95% confidence interval = 0.87–1.37). Using multivariate analysis we found that treatment was more likely to fail in children who were not given the medicine correctly (P = 0.001), in those younger than 12 months (P = 0.004), those who had used antibiotics previously (P = 0.002), those whose respiratory rate was  20 breaths/minute above the age-specific cut-off point (P = 0.006), and those from urban areas (P = 0.042). Conclusion Both standard and double strength cotrimoxazole were equally effective in treating non-severe pneumonia. Close followup of patients is essential to prevent worsening of disease. Definitions of clinical failure need to be more specific. Surveillance in both rural and urban areas is essential in the development of treatment policies that are based on clinical outcomes.